PROBLEMS AND CAUSING FACTORS IN THE DEVELOPMENT OF FERGANA CITY PUBLIC TRANSPORT - F. A. Omonov; V. I. Jorayev (European Science Publishing, 2023)
The article deals with the issue of eliminating transport problems in areas that are currently of great importance at the level of the Republic and approved by the presidential decree.
Keywords: bus, public transport, intersection, station, infrastructure, corruption, decision, parking meter.